2023
DOI: 10.3390/su15043768
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Demographics and Previous Experience in Tourists’ Experiential Perceptions

Abstract: Tourism experiences are personal events characterized by their subjective nature. Because of this, each consumer has his or her way of perceiving the experience depending on their individual characteristics. The literature suggests that demographic and prior experience variables are factors that may influence tourists’ perceptions. While some studies have examined the influence of these factors on marketing variables, more information is still needed to help predict tourists’ behavior and to understand how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 79 publications
(138 reference statements)
3
5
0
Order By: Relevance
“…Although the data of this study showed a non-normal distribution, a t-test for independent samples was used to determine whether the evaluations of experiential quality and post-consumption behaviours including perceived value, overall satisfaction, and behavioural intentions differed according to gender, first-time or repeat visitors and type of theme park visited. The t-test for independent samples is a popular parametric test for comparing two groups (Pasaco-González et al, 2023). Even if the study's data revealed a non-normal distribution, the parametric test nevertheless yield reliable results even when the normality assumptions are broken.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the data of this study showed a non-normal distribution, a t-test for independent samples was used to determine whether the evaluations of experiential quality and post-consumption behaviours including perceived value, overall satisfaction, and behavioural intentions differed according to gender, first-time or repeat visitors and type of theme park visited. The t-test for independent samples is a popular parametric test for comparing two groups (Pasaco-González et al, 2023). Even if the study's data revealed a non-normal distribution, the parametric test nevertheless yield reliable results even when the normality assumptions are broken.…”
Section: Methodsmentioning
confidence: 99%
“…Experiential quality is important for judging tourists' subjective emotions. Additionally, it is a significant predictor of satisfaction and behavioural intentions (Pasaco-González et al, 2023). It is critical to look into consumer experiences in the tourism sector from both a theoretical and practical aspect because tourist services are hedonic and provide consumer experiences (Wu et al, 2018b).…”
Section: Experiential Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, gender also exerts significant influences on travellers’ behaviour. The studies of Oh et al (2002) and Pasaco-González et al (2023) show that female and male tourists form different levels of expectations and perceptions; hence, they may demonstrate different levels of satisfaction and loyalty. Last but not least, travel formats, including independent travel and group travel, were also confirmed to influence tourists’ satisfaction and loyalty.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%